ANALISIS PENGARUH NET PROFIT MARGIN, RETURN ON ASSETS, TOTAL ASSETS TURNOVER, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN (Studi Pada : Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2010-2016) - Wahyu, Dzulfikar Dwi; Mahfud, Mohammad Kholiq (Diponegoro Journal of Management, 2018)
There has been a lot of research that discusses the value of the company, but still found research gap or differences in results from studies that have been done before. Inequality from the results of previous studies encourages further testing to determine the consistency of findings on firm value. Firm value is a description of the current value of expected earnings in the future and as an indicator for the market to assess a company as a whole. The higher of firm value is the more willing investors in paying a piece of stock. This study aims to examine the effect of net profit margin, return on assets, total asset turnover, earnings per share, and debt to equity ratio to firm value represented by price to book value.The sample used in this study were 57 manufacturing companies listed on BEI during period 2010-2016. The analyticals method used in this research is multiple linear regression with classical assumption test such as autocorrelation test, heteroscedasticity test, multicolinearity test, and determination coefficient test, F statistic test, and t statistic test.The results of this study show that net profit margin, return on assets, and debt to equity ratio have a positive and significant effect on price to book value, while total asset turnover and earnings per share have no effect on price to book value.